Meningkatkan Faktor-Faktor Kepuasan Pelanggan Perusahaan Retail Dengan Nilai Ergo-Ikonik Dan Lingkungan Layanan - Samuel, Yosua Pardamean; Kurniawati, Kurniawati; Harsasi, Meirani (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The customer is one thing that is very important and must be considered by all companies, including companies engaged in retail. Not a few retail companies close their outlets because customers feel dissatisfied so choose their competitors. Therefore, there is a need for research on the factors that determine customer satisfaction in retail companies. This research will use the Smart-PLS 03 software to determine the factors that affect the service environment, customer satisfaction, and how the relationship between service environment and customer satisfaction. Based on the analysis obtained that tangible, iconic, price, ergo, empathy are variables that have a significant and significant effect. As for the other variables, namely assurance and responsiveness have a positive but not significant effect. While the level of influence with customer satisfaction, price, empathy, and iconic ergo variables have a significant and positive effect both directly and indirectly so that the service environment has a partial mediating effect. On the other hand, for tangible variables, guarantees, responsiveness and have a positive and insignificant effect on direct influence. But when the indirect effect becomes a positive and significant effect. So that the environment has a full mediation in service with customer satisfaction. In closing, the results obtained that the service environment has a positive and significant effect on customer satisfaction.